50.1k views
4 votes
StartFraction (negative 7) squared Over (negative 7) Superscript negative 1 EndFraction

User Sansalk
by
5.4k points

2 Answers

1 vote

Answer:

-343

Explanation:

User Ppuppim
by
6.4k points
1 vote

Answer:

-343

Explanation:

Given the expression:
((-7)^2)/((-7)^(-1))

You will notice that the terms in the numerator and denominator have the same base (-7).

This makes it very easy to simplify by applying the division law of indices.


(a^x)/(a^y) =a^(x-y)

Therefore:


((-7)^2)/((-7)^(-1))=(-7)^(2-(-1))\\=(-7)^(2+1)\\=(-7)^3\\=-7 X -7 X -7\\=-343

User Homer Xing
by
5.4k points